Mental distress links with physical activities, sedentary lifestyle, social support, and sleep problems: A Syrian population cross-sectional study - Swed, Sarya; Alibrahim, Hidar; Bohsas, Haidara; Nashwan, Abdulqadir J.; Elsayed, Mohamed; Almoshantaf, Mohammad B.; Kadri, Saeed A.; Sawaf, Bisher; Albuni, Mhd Kutaiba; Battikh, Elias; Elkalagi, Nashaat K.; Ahmed, Safaa M.; et al. (Frontiers in Psychiatry, 2023)
Background: Mental illnesses are very common and difficult to manage, impacting roughly 12% of the worldwide population in 2019; however, adolescence is a critical period for the development of many diseases and future health habits. Medical literature has shown that solitude is a strong predictor of depression symptoms; additionally, social connectivity is essential to human life, so social relationship impairments are likely to cause depression. Mental health treatment is needed in Syria's war areas, camps of refugees, and displaced people within the country's borders, where conflict and migration have resulted in a high rate of trauma and significant mental illnesses among Syrians. This study adds to the literature by searching for possible links between these ranges of controllable variables and adding more information about Syria's mental health. Methods: An online quantitative cross-sectional study was conducted between March and April 2022 in all 14 municipalities in Syria, using a structured questionnaire that assesses data on behaviors of health, health in general, well-being, and adult population quality of life. Results: Among 1224 respondents (371 men and 853 women), women have shown higher levels of mental distress, sleep issues, low levels of engagement in structured activities, and a difficult work environment than men. Women who are experiencing mental anguish have reported being more sedentary, participating in less scheduled activities, and receiving less social support. Conclusions: High sedentary time was found to have measurable links with women in mental distress. Low levels of engagement in structured activities and low leisure-time physical activity were observed in mental health distressed Syrian women. Sleep problems and hard financial were both seen in subjects with mental illness in both sexes.